A Comparative Study of the Dimensions of Military Pedagogy in Islamic Countries (Case study:Officer University of Army, Islamic Republic of Iran and Malaysian University of Defense ) - Pejman Salehi; Seyfollah Fazlloahi; Aliakbar Khoshgoftar (علوم و فنون نظامی, 2018)
Comparative study is one of the scientific methods through which the similarities, differences, experiences and achievements of other countries can be found in different scientific and specialized fields and the results can be used to achieve the desired situation. The aim of this paper is the comparative study of Islamic countries in the field of military pedagogy, in which Iran and Malaysia, from the perspective of military pedagogical indicators in the period after the victory of the Islamic Revolution under the leadership of Imam Khomeini (1979) and the Malaysian Revolution, The leadership of Mahathir Mohammad (in 1981) has been studied, and as a result, it has been studied and studied the status of military education in accordance with the key pedagogical indicators in the military higher education centers of the two countries. The method of this research is documentary-comparative study using content analysis method. The results of this study show that after the 1979 Islamic Revolution in Iran, almost equal to the Malaysian Revolution by Mahathir Mohammed in 1981; Iran's pedagogical achievements in higher military education have been more significant